Teaching Vocabulary Through Spelling Strategy on Students’ Proficiency in Dictated Writing Achievement of The Eleventh Grade Students at SMP Negeri 1 Siborongborong - Rekolina Siahaan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research work aims at evaluating the importance of the introduction of spelling as a vocabulary strategy for students in the teaching of English as a foreign language at senior high school level, and how this can be a beneficial tool as input for the acquisition of new vocabulary, then a helpful means to produce a correct writing. To attain such an aim, the researcher administered a pre-test and a post-test. The former was intended to determine the pre-instructional knowledge of the graphic form of words, whereas the latter was aimed at finding out whether the spelling strategy implemented during instruction was effective in enhancing the subjects’ ability to write with less spelling mistakes. The test was interposed by two sequential lessons. The results of this innovative investigation have confirmed the hypothesis which states that if we train students to pay a careful attention to the form of words this would help them to spell them and write correctly. The learners under investigation proved to have learnt most of the vocabulary items of the proposed text.